Geographies of Contact Britain, the Middle East and the Circulation of Knowledge - Lehni, Caroline; Moghaddassi, Fanny; Ibata, Hélène; Nasiri-Moghaddam, Nader (Études orientales, slaves et néo-helléniques, 2017)
This interdisciplinary collection of essays, in keeping with recent historiographic approaches to East-West cultural relations, focuses on the material and spatial conditions of cultural encounters between Britain and the Middle East, from the late Middle Ages to the dawn of the twentieth century. By exploring a diversity of contexts and sites of encounter (from cosmopolitan cities to private collections), and by underlining the manifold nature of cultural exchanges connected with them, the essays outline the dynamic and complex interplay which contributed to the circulation of knowledge between these regions. They also bring together a variety of practices (diplomatic, geographical, aesthetic, archaeological, literary or commercial) in order to highlight the multi-layered dimension of these cultural transfers and exchanges.